Analysis of results from a collaborative study of the dominant lethal assay - James, Derek A.; Smith, David M. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1982)
A dominant lethal (DL) mutation is a genetic change that results in the death of the conceptus that inherits it. The assya is normally carried out in mice and the production of DL mutation by the test chemical is characterised by an increase in non-viable embryos. A distinct advantage of the DL assay is that it is an in vivo, mammalian, germ cell assay and is therefore pertinent to the fundamental question of chemical mutagenesis, i.e.: is a chemical likely to produce genetic changes that can be transferred to the offspring? The two principal criticisms of the assay are that the main type of genetic damage it detects is chromosomal breakage that leads to the conceptus, and that the assay is considered to be relatively insensitive. The Association of the British Pharmaceutical Industry (ABPI) Working Party on Mutagenicity was established in 1974. Its principal objective was to consider the problem of mutagenicity and associated matters in relation to the development of new medicines and to make recommendations and proposals for collaborative work if indicated. The dominant lethal assay is one of several tests for mutagenicity chosen for evaluation by collaborative study. The objective of the collaborative study was to gain more information about the validity and dependability of the dominant lethal assay. The present report concerns an analysis of the differences between compounds, laboratories and statistical methods utilising the data from the collaborative study.